Wybrane zagadnienia dziedziczenia testamentowego w świetle orzecznictwa sądów apelacji lwowskiej w okresie międzywojennym - Koredczuk, Józef (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
in question is further enhanced by references to the case-law of courts forming the Lviv judicialdistrict, illustrating the complexity of the provisions. The case-law testifies to how big a role wasplayed by testate succession in the part of Poland annexed by Austria. On the other hand, it showshow many people did not know the ABGB provisions and how differently the provisions wereinterpreted by the courts.Keywords: Lviv judicial district, Austrian Civil Code, testate succession, inter-war period,case-law
Keywords: prawo spadkowe; zabór austriacki; okres międzywojenny; dziedziczenie; testamenty; spadkobiorca; spadkodawca